ANALISIS RISIKO PASAR BERBASIS REVOLUSI INDUSTRI 4.0 DAN KETERSEDIAAN TEKNOLOGI TERHADAP RETURN SAHAM SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA 2020-2023 - Ni Kadek Desy Rahayu; Ni Luh Kardini; Ni Putu Yuli Tresna Dewi (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to analyze the effect of the Industrial Revolution 4.0 and the availability of technology on mining sector stock returns on the Indonesia Stock Exchange (IDX) for the 2020-2023 period, by considering the role of market risk as a moderating variable. This study uses secondary data obtained from financial reports and annual reports of mining companies listed on the IDX, with a sample of 12 companies selected using purposive sampling method. Multiple regression analysis was used to test the research hypothesis. The results showed that the Industrial Revolution 4.0, technology availability and market risk had a positive and significant effect on mining sector stock returns. Industrial Revolution 4.0 and technology availability had a positive and significant effect on market risk. In addition, market risk is proven to positively moderate the relationship between Industrial Revolution 4.0 and technology availability with stock returns, which means that the positive effect of these two variables on stock returns is stronger in conditions of high market risk. This study provides empirical evidence regarding the importance of adaptation to the Industrial Revolution 4.0 and investment in technology for mining companies to improve their stock performance, especially in the face of high market risk.